Effect of restrictions on television food advertising to children on exposure to advertisements for 'less healthy' foods: repeat cross-sectional study. - Jean Adams; Rachel Tyrrell; Ashley J Adamson; Martin White (PLoS ONE)
Background In 2007, new scheduling restrictions on television food advertising to children in the UK were announced. The aim of the restrictions was to "reduce significantly the exposure of children under 16 to high fat, salt or sugar (HFSS) advertising". We explored the impact of the restrictions on relative exposure to HFSS food advertising among all viewers and among child television viewers, as well as adherence to the restrictions. Methods We conducted two cross-sectional studies of all advertisements broadcast in one region of the UK over one week periods--the first (week 1) six months before the restrictions were introduced, and the second (week 2) six months after. Data on what products were advertised were linked to data on how many people watched each advertisement. Nutritional content of foods advertised was added to the dataset and used to calculate HFSS status. Relative exposure was calculated as the proportion of all advertising person-minute-views (PMVs) that were for HFSS foods. Results 1,672,417 advertising PMV were included. 14.6% of advertising PMV were for food and 51.1% of these were for HFSS food. Relative exposure of all viewers to HFSS food advertising increased between study weeks 1 and 2 (odds ratio (99% confidence intervals) = 1·54 (1·51 to 1·57)). Exposure of children to HFSS food advertising did not change between study weeks 1 and 2 (odds ratio (99% confidence intervals) = 1·05 (0·99 to 1·12)). There was almost universal adherence to the restrictions. Conclusions Despite good adherence to the restrictions, they did not change relative exposure of children to HFSS advertising and were associated with an increase in relative exposure of all viewers to HFSS advertising. Stronger restrictions targeting a wider range of advertisements are necessary to reduce exposure of children to marketing of less healthful foods.